E-Participation in Semarang Smart City - Pradana, Satria Adhi; Astuti, Retno Sunu; Ningsih, Tri Yuni; Afrizal, Teuku (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Era 4.0 in the context of e-government is less relevant for discussing smart cities. Because smart city is not only about public services, but smart city has developed into a means of realizing community participation who are involved in government activities. Semarang Smart City is one of the Smart City products which is quite good and general with the conditions of other cities that apply smart cities as well. Using netnographic methods and literature studies by collecting data, information, research journals, books, and literature from trusted sources in written and digital form that are relevant to this research. In this paper, the author will describe several forms of e-participation in the Semarang City Smart City program. Semarang Smart City has been able to provide open services, a place for community aspirations. By knowing the form of e-participation that is applied in Semarang Smart City, it is hoped that it can provide an overview of other local governments that implement smart city programs to better understand the smart city program, and can realize various participatory and collaborative decision-making that is right on target in order to create a highly respected government. high transparency and accountability.